Polyclonal antibodies as a feed additive for cattle adapted or not adapted to highly fermentable carbohydrate diets - Barros, Tarley A.; Cassiano, Eduardo C. O.; Marino, Carolina T.; Pacheco, Rodrigo D. L.; Ferreira, Fernanda A.; Junior, Flavio Perna; Martins, Maurício F.; Meyer, Paula M.; Millen, Danilo D. [UNESP]; Arrigoni, Mário D. B. [UNESP]; Rodrigues, Paulo H. M. (Taylor & Francis, 2019)
The effect of a polyclonal antibody preparation (PAP) against Streptococcus bovis and Fusobacterium necrophorum on ruminal fermentation and digestion in ruminally cannulated cows was investigated in two 3 × 3 Latin squares in factorial arrangement of treatments 3 × 2 regarding two feed additives (PAP in powder (PAPP) and in liquid (PAPL) presentation) plus control (CON) and two managements of diets (with or without adaptation to highly fermentable carbohydrate diets). Adapted group had greater DMI (p < 0.0001) and DM (p < 0.0001), NDF (p = 0.03) and total carbohydrates (p < 0.0001) apparent digestibility when compared to non-adapted group. PAPL had greater DM (p = 0.02), NDF (p = 0.03) and total carbohydrates apparent digestibility when compared to PAPP or CON. Adapted animals had lower (p < 0.0001) rumen pH when compared to non-adapted animals. Moreover, PAPL group had greater (p = 0.04) rumen pH values when compared to PAPP and CON. PAPL showed potential effect as an additive by increasing apparent digestibility of DM, NDF and total carbohydrates and also for being more efficient to prevent the drop in rumen pH during the peak of fermentation.
Keywords: Passive immunization; ruminal fermentation; total tract apparent digestibility